Intelligent Control System of Fire-Extinguishing and Obstacle-Avoiding Hexapod Robot - Qory Hidayati; Fathur Zaini Rachman; Nur Yanti (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2018)
This hexapod fire extinguisher robot is constructed based on technological developments evolving very rapidly, especially in the field of robotics technology. The hexapod robot has become a big concern in the development of robotics technology with many existing contests of hexapod robot. This hexapod fire extinguisher robot is designed based on Fuzzy Mamdani Logic. The navigation of fire extinguisher hexapod robot is based on distance detection with ultrasonic sensor determining the movement of robot’s legs utilizing Fuzzy Logic. A fire extinguisher hexapod robot will explore a tunnel arena having several rooms created for the robot to explore. This hexapod robot uses Arduino as a microcontroller and uses 18 servo motors in which each foot requires 3 servo motors. Moreover, good navigation will be aimed by utilizing Fuzzy Logic in the hexapod robot design. The application of many rules on Fuzzy Logic makes the better navigation; furthermore, the results present the ultrasonic sensor having an average error of 1.256%, the Fuzzy Logic applied showing 0% error, and the overall success rate presenting approximately 80%.